Culturally Responsive Chemistry Teaching (CRCT) of College Students as A Novice Teacher: Does It Matter? - Winarti, Atiek; Almubarak, Almubarak; Saadi, Parham; Ijirana, Ijirana; Aminah, Siti; Ratman, Ratman (JTK (Jurnal Tadris Kimiya), 2022)
Culture is an essential part of human life; cultural involvement in learning can train students to find the meaning of life, including the contribution of chemistry in the cultural context of society. Teachers reported that they struggle to meet students' needs relevant to differences in culture and ability. The study aimed to investigate college students' understanding of chemistry by involving their culture with various methods, including transformative teaching and problem-solving. The research method used descriptive with a qualitative approach. The data collection techniques were projects, interviews, observation, and questionnaires. The findings revealed that the learning process involving cultural aspects could show the contribution of chemical elements in society, especially the formation of scientific cognition. Culturally responsive chemistry teaching is an innovative learning approach to training college students' understanding (novice teachers). The research concludes that a good chemistry teacher can understand the needs of students, especially knowing their cultural background. To effectively teach from diverse backgrounds, schools need teachers who understand the impact of student's home and community cultures on their educational experience. This research can also develop an instructional design, train novice chemistry teachers’ teaching skills, and develop curriculum.